Human relations in organizations applications and skill building - Lussier, Robert N. (McGraw Hill LLC, 2022)
"Human Relations in Organizations 12th edition, is designed to be flexible enough to be used with the traditional lecture method while offering a wide range of engaging in-class and online activities"--